Loss of EphA7 Expression in Basal Cell Carcinoma by Hypermethylation of CpG Islands in the Promoter Region. (22nd January 2022) - Liu, Jie; Yu, Na; Feng, Xiao; He, Yan; Lv, Kang; Zhu, Haiping; Wang, Jiandong
Abstract : Basal cell carcinoma (BCC) is the most common malignancy worldwide, with increasing incidence. BCCs present low mortality but high morbidity, and its pathogenesis remains unclear. Eph receptors have been implicated in tumorigenesis. EphA7 plays a role as a tumor suppressor in certain cancers. We checked EphA7 expression levels and methylation status in a set of BCCs, benign skin diseases, and compound nevus tissue samples using immunohistochemistry. EphA7 protein was positively expressed in normal basal cells, benign skin diseases, and compound nevus cells, but lost in areas of BCC tissues. We detected hypermethylation in BCC tissue samples with reduced expression of EphA7. There is a significant relationship between the expression level of EphA7 receptor protein and the methylation status of CpG islands in the EphA7 promoter region (P < 0.001 ). To our knowledge, this is the first study to report the EphA7 expression profile and hypermethylation of EphA7 in BCC. The role of the EphA7 gene and the status of hypermethylation in tumorigenesis and treatment of BCC warrant further investigation.